Correlative Microscopy of Bone in Implant Osteointegration Studies - Alessandra Triré; Désirée Martini; Ester Orsini; Marco Franchi; Viviana De Pasquale; Beatrice Bacchelli; Mario Raspanti; Alessandro Ruggeri; Vittoria Ottani (The Scientific World Journal)
Routine morphological analyses usually include investigations by light microscopy (LM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Each of these techniques provides specific information on tissue morphology and all the obtained results are then combined to give an in-depth morphological overview of the examined sample. The limitations of this traditional comparative microscopy lie in the fact that each technique requires a different experimental sample, so that many specimens are necessary and the combined results come from different samples. The present study describes a technical procedure of correlative microscopy, which allows us to examine the same bone section first by LM and then, after appropriate processing, by SEM or TEM. Thanks to the possibility of analyzing the same undecalcified bone sections both by LM and SEM, the approach described in the present study allows us to make very accurate evaluations of old/new bone morphology at the bone-implant interface.